The Role of Islamic Religious Education (PAI) Teachers in Shaping the Religious Character of Students - Santika, Felia (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2023)
The important role of Islamic religious education (PAI) teachers in shaping students' religious character attracted researchers to investigate. The purpose of this review is to determine the role of Islamic religious education (PAI) teachers in shaping students' religious character. There are several articles regarding reviews of the role of Islamic religious education (PAI) teachers in shaping students' religious character that can be found and this article discusses the results of the literature review carried out by the author. The research process begins with a search engine (Google Scholar) to search for articles then conclusions are drawn, the search ranges from 2016-2022. Based on the results of the literature review, research mostly shows that the role of Islamic religious education (PAI) teachers in shaping students' religious character has an impact. that Islamic religious education has an important role in character formation, more specifically religious character which is rooted in faith learning, educating students to become human beings with religious character.